Religiosity and Spirituality in the Financial Behavior of Credit Cooperative Members - Angjelina Christi Endi; Rolland Fanggidae; Wehelmina M Ndoen (Universitas Nusa Cendana, 2022)
This study aims to determine the effect of religiosity and spirituality on the financial behavior of members of Cooperative Credit Permata Bunda Paroki Waelengga. This research is a quantitative research using the survey method. This study's population were all Cooperative Credit Permata Bunda members. This study used simple random sampling with a sample of 100 members. The data analysis technique used simple linear regression with the help of SPSS Version 16.0 software. The results showed that the religiosity variable had a positive but not significant effect on the financial behavior variable, the spirituality variable had a positive but not significant effect on the financial behavior variable, and the religiosity and spirituality variables together had a positive but not significant effect on the financial behavior variable.